2013
DOI: 10.1371/journal.pone.0069620
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Protects Epithelial Cells from Excessive Autophagy and Apoptosis in Experimental Neonatal Necrotizing Enterocolitis

Abstract: Neonatal necrotizing enterocolitis (NEC) is a devastating gastrointestinal disease of preterm infants. Increased intestinal epithelium permeability is an early event in NEC pathogenesis. Autophagy and apoptosis are induced by multiple stress pathways which may impact the intestinal barrier, and they have been associated with pathogenesis of diverse gastrointestinal diseases including inflammatory bowel disease. Using both in vitro and in vivo models, this study investigates autophagy and apoptosis under experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 64 publications
6
69
0
Order By: Relevance
“…In contrast, apoptosis may be the primary method of death of the initial intestinal mucosa cells, which may be achieved through TNF-α and other factors that induce mitochondrial dysfunction and activate the mitochondrial apoptosis cascade. It has been verified in an experimental NEC model that cell autophagy and apoptosis were activated, cell autophagy occurred before the occurrence of apoptosis, and the occurrence of intestinal necrosis was after cellular apoptosis [10]. A recent study has found that CDP-choline in NEC neonatal rats can significantly reduce cellular apoptosis and the level of activated caspase-3, which supported the results of this study.…”
Section: (A) the Control Group (×400) (B) Nec Model Group (×400) supporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, apoptosis may be the primary method of death of the initial intestinal mucosa cells, which may be achieved through TNF-α and other factors that induce mitochondrial dysfunction and activate the mitochondrial apoptosis cascade. It has been verified in an experimental NEC model that cell autophagy and apoptosis were activated, cell autophagy occurred before the occurrence of apoptosis, and the occurrence of intestinal necrosis was after cellular apoptosis [10]. A recent study has found that CDP-choline in NEC neonatal rats can significantly reduce cellular apoptosis and the level of activated caspase-3, which supported the results of this study.…”
Section: (A) the Control Group (×400) (B) Nec Model Group (×400) supporting
confidence: 88%
“…It has been shown that intestinal mucosal permeability was an early event in the onset of NEC in premature infants. Moreover, we found that apoptosis and autophagy occurred during this process [10]. Our investigation also found that the expression of beclin-1 and LC3II in the NEC model group was stronger than those in the normal group and the CDP-choline group, whereas there were no differences between the NEC+CDP-choline treatment group and the other groups; hence, it was suggested that CDP-choline reduced autophagy and apoptosis and manifested a protective effect on the intestine.…”
Section: (A) the Control Group (×400) (B) Nec Model Group (×400) supporting
confidence: 55%
“…Our laboratory has discovered the induction of autophagy in the intestinal epithelium of NEC patients and in the rat NEC model (38). Recently, our initial observation was confirmed in the rat and mouse NEC models (43,60).…”
mentioning
confidence: 80%
“…Under this situation, erythropoietin, a breast milk component that downregulates autophagy via the Akt/mTOR signaling pathway has been shown to preserve the intestinal barrier function and decrease the incidence of NEC. 63 The extent of autophagy induction is also a deciding factor for the outcome of autophagy induction. Among the 2 mTOR complexes that regulate autophagy, mTORC1 and mTORC2, sustained AMP-activated protein kinase (AMPK) activation of ERK MAPK has been shown to cause disassembly of mTORC2 via marked increase in beclin 1 expression, leading to cytodestructive autophagy.…”
Section: Importance Of the Context For Autophagy Regulation Of Cell Jmentioning
confidence: 99%